2001
DOI: 10.1142/s0219493701000102
|View full text |Cite
|
Sign up to set email alerts
|

Modeling a Simple Choice Task: Stochastic Dynamics of Mutually Inhibitory Neural Groups

Abstract: We describe the dynamical and bifurcational behavior of two mutually inhibitory, leaky, neural units subject to external stimulus, random noise, and "priming biases". The model describes a simple forced choice experiment and accounts for varying levels of expectation and control. By projecting the model's dynamics onto slow manifolds, using judicious linear approximations, and solving for one-dimensional (reduced) probability densities, analytical estimates are developed for reaction time distributions and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 20 publications
2
67
0
Order By: Relevance
“…Thus, our model in regime II can perform decision computation ( Fig. 13 A, C) without working memory function, similar to previously studied connectionists models (Brown and Holmes, 2001;Usher and McClelland, 2001). Furthermore, we found that, for the whole range of 0 , the unstable time constant of the saddle point is of a few seconds, an order of magnitude greater than the stable time constant (Fig.…”
Section: Two Distinct Regimes Of Decision-making Dynamicssupporting
confidence: 85%
See 4 more Smart Citations
“…Thus, our model in regime II can perform decision computation ( Fig. 13 A, C) without working memory function, similar to previously studied connectionists models (Brown and Holmes, 2001;Usher and McClelland, 2001). Furthermore, we found that, for the whole range of 0 , the unstable time constant of the saddle point is of a few seconds, an order of magnitude greater than the stable time constant (Fig.…”
Section: Two Distinct Regimes Of Decision-making Dynamicssupporting
confidence: 85%
“…Such a reduction represents a significant step in bridging the gap between the biologically based model of Wang (2002) and abstract mathematical models, and allow for a comparison between our model and previously proposed models of decision making. Like other models (Usher and Cohen, 1999;Brown and Holmes, 2001;Usher and McClelland, 2001;Machens et al, 2005), our model is a nonlinear dynamical system that can be conceptualized as a circuit of neural populations coupled effectively by mutual inhibition. However, it is important to emphasize that recurrent excitation plays an indispensible role in producing reverberatory dynamics underlying winner-take-all competition in our model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations